COSMETIC RECONSTRUCTION AND RESTORATION WITH COMPOSITE RESIN USING THE DIRECT TECHNIQUE FOR REANATOMIZATION OF CANINES IN LATERAL INCISORS - CASE REPORT (CIPEEX, 2025)
The concept of beauty in modern society has made people more demanding and detail-oriented, and very challenging for dental surgeons to meet so many aesthetic demands. Teeth with any type of alteration negatively affect harmony, causing individuals to seek solutions to restore naturalness. This quest for perfection has led to the evolution of dental materials, aiming at the most faithful reproduction of the natural. Objective: To report a clinical case in which the patient presented bilateral agenesis of the upper lateral incisors, providing an aesthetic solution through recontouring and reanatomization with composite resin of the upper canines, leaving them with a shape similar to the lateral incisors. Case report: The patient, DROM, female, attended the UniEVANGÉLICA Dental Clinic with the main complaint that "her smile was different from other people's, and that her canines were more forward, leaving spaces between her teeth." The intraoral clinical examination revealed bilateral absence of the upper lateral incisors. The canines were positioned in place of the missing teeth, leaving the incisal edges quite open. The proposed treatment was to recontour and reanatomize the upper canines into lateral incisors with composite resin, changing the shape and reducing the spaces between the incisal edges. This was followed by wear on the crown of the upper canines and the clinical protocol for composite resin, inserting layers to complement the details of the shape of the lateral incisors. Conclusions: The immediate result met the patient's aesthetic expectations, and the use of composite resins demonstrated their versatility in various clinical situations.
Keywords: Anodontia; Dental aesthetics; Composite resins; Self-image